The impacts of an mHealth intervention targeting parents on health service usage and out‐of‐pocket costs in the first 9 months of life: The Growing healthy app - Rachel A. Laws; Miaobing Zheng; Vicki Brown; Sharyn Lymer; Karen J. Campbell; Catherine G. Russell; Sarah Taki; Eloise Litterbach; Kok‐Leong Ong; Elizabeth Denney‐Wilson (Wiley, 2024)
Abstract Mobile health (mHealth) interventions provide a low‐cost, scalable approach to supporting parents with infant feeding advice with the potential to reduce health care visits and associated costs for infant feeding support. This Australian study examined the impact of the Growing healthy (GH) app on health service utilisation and out‐of‐pocket costs for families in the first 9 months of their infants life. A quasi‐experimental study with a comparison group was conducted in 2015-2016 with an mHealth intervention group (GH app, n = 301) and a nonrandomized usual care group (n = 344). The GH app aimed to support parents of young infants with healthy infant feeding behaviours from birth to 9 months of age. App‐generated notifications directed parents to age‐and feeding‐specific content within the app. Both groups completed surveys at baseline when infants were less than 3 months old (T1), at 6 months (T2) and 9 months (T3) of age. At T3, participants reported health services used and any out‐of‐pocket costs for advice on infant feeding, growth or activity. App users had lower odds (odds ratio: 0.38 95% confidence interval: 0.25, 0.59) of using one or more services and had lower number of visits to a general practitioner (1.0 vs. 1.5 visits, p = 0.003) and paediatrician (0.3 vs. 0.4 visits, p = 0.049) compared to the usual care group. There was no difference in out‐of‐pocket costs between groups. Provision of an evidenced‐based infant feeding app may provide substantial savings to the health system and potentially to parents through fewer primary health care and paediatrician visits.